Arctigenin Suppressed Epithelial-Mesenchymal Transition Through Wnt3a/β-Catenin Pathway in PQ-Induced Pulmonary Fibrosis - Gao, Fei; Zhang, Yun; Yang, Zhizhou; Wang, Mengmeng; Zhou, Zhiyi; Zhang, Wei; Ren, Yi; Han, Xiaoqin; Wei, Mei; Sun, Zhaorui; Nie, Shinan (Frontiers in Pharmacology, 2020)
Arctigenin (ATG), a major bioactive substance of Fructus Arctii, counters renal fibrosis; however, whether it protects against paraquat (PQ)-induced lung fibrosis remains unknown. The present study was to determine the effect of ATG on PQ-induced lung fibrosis in a mouse model and the underlying mechanism. Firstly, we found that ATG suppressed PQ-induced pulmonary fibrosis by blocking the epithelial-mesenchymal transition (EMT). ATG reduced the expressions of Vimentin and α-SMA (lung fibrosis markers) induced by PQ and restored the expressions of E-cadherin and Occludin (two epithelial markers) in vivo and in vitro. Besides, the Wnt3a/β-catenin signaling pathway was significantly activated in PQ induced pulmonary fibrosis. Further analysis showed that pretreatment of ATG profoundly abrogated PQ-induced EMT-like phenotypes and behaviors in A549 cells. The Wnt3a/β-catenin signaling pathway was repressed by ATG treatment. The overexpression of Wnt3a could weaken the therapeutic effect of ATG in A549 cells. These findings suggested that ATG could serve as a new therapeutic candidate to inhibit or even reverse EMT-like changes in alveolar type II cells during PQ-induced lung fibrosis, and unraveled that the Wnt3a/β-catenin pathway might be a mechanistic tool for ATG to control pulmonary fibrosis.